Modulating root system architecture: cross-talk between auxin and phytohormones - Jan, Mehmood; Muhammad, Sajid; Jin, Weicai; Zhong, Wenhao; Zhang, Shaolong; Lin, Yanjie; Zhou, Yueni; Liu, Jinlong; Liu, Haifeng; Munir, Raheel; Yue, Qiang; Afzal, Muhammad; et al. (Frontiers in Plant Science, 2024)
Root architecture is an important agronomic trait that plays an essential role in water uptake, soil compactions, nutrient recycling, plant-microbe interactions, and hormone-mediated signaling pathways.Recently, significant advancements have been made in understanding how the complex interactions of phyto-hormones regulate the dynamic organization of root architecture in crops. Moreover, phytohormones, particularly auxin act as internal regulators of root development in soil, starting from the early organogenesis to the formation of root hair (RH) through diverse signaling mechanisms. However, a considerable gap leftovers in understanding the hormonal cross-talk during various developmental stages of roots. This review examines the dynamic aspects of phytohormone signaling, crosstalk mechanisms, and the activation of transcription factors (TFs) throughout various developmental stages of the root life cycle. Understanding these developmental processes, together with hormonal signaling and molecular engineering in crops, can improve our knowledge of root development under various environmental conditions.